RUSSIAN RESEARCH AND HIGHER EDUCATION SYLLABI ON POST-SOVIET SPACE: PRIORITIES IN TERMINOLOGY AND STRUCTURE OF COURSES - Y. A. Nikitina (Vestnik MGIMO-Universiteta)
The article is devoted to the analysis of the key concepts used in the undergraduate and graduate courses on the post-Soviet region, of the link between these concepts and the official rhetoric based on the foreign policy documents. Major research questions of the article are: how is the international political region on the ex-Soviet space is called? Are there any subregions in this region? Is more attention paid to the analysis of regional organizations compared to the analysis of national specificities or bilateral and multilateral relations not related to regional institutions? Does the structure of the Russian courses correspond to the structure of courses taught at Western universities? The results of the analysis demonstrate that the structure of the academic courses and, partially, of the PhD dissertations on economic and political processes on the post-Soviet space correspond to the priorities in the Russian official documents: for instance, the same terminology is used to describe the whole international political region (the post-Soviet space) and subregions (Central Asia and Caucasus); more priority is given to the analysis of institutionalized cooperation in the framework of international organizations (first of all, the CIS); the role of Russia in the region, its interests and its participation in regional processes are usually understudied, or is absent from the academic courses. The analysis showed that currently there are no so many textbooks on the post-Soviet space, despite the fact that the course "Economic and political processes in the CIS" is included in the basic part of the Professional cycle of the Federal State Educational Standard on the International Relations. However, it should be noted that in the federal educational standards the content of the courses is not specified, that is why universities have an opportunity to create their original content, even if the title of the course is pre-determined.